Team Leadership: School Boards at Work - Rosenberger, Michal (Rowman & Littlefield Publishers, 1998)
Local school boards are responsible for the two most important issues in most people's lives: their children and their money. Why do these governing bodies fail to develop into high-performance teams? This book answers this question and provides techniques for districts to solve their underlying governance problems. Discusses the complexities of group dynamics, strategies for effective team governance, leadership functions of the local board and their role in school improvement, and the complexities of school politics.